H4SiW12O40-catalyzed oxidation of nitrobenzene in supercritical water: kinetic and mechanistic aspects - Arslan-Alaton, Idil; Ferry, John L. (Elsevier BV, 2002)
Abstract The catalytic effect of a heteropolyacid, H4SiW12O40, on nitrobenzene (20 and 30 μM) oxidation in supercritical water was investigated. A capillary flow-through reactor was operated at varying temperatures (T=400–500 °C; P=30.7 MPa) and H4SiW12O40 concentrations (3.5–34.8 μM) in an attempt to establish global power-law rate expressions for homogenous H4SiW12O40-catalyzed and uncatalyzed supercritical water oxidation. Oxidation pathways and reaction mechanisms were further examined via primary oxidation product identification and the addition of various hydroxyl radical scavengers (2-propanol, acetone, acetone-d6, bromide and iodide) to the reaction medium. Under our experimental conditions, nitrobenzene degradation rates were significantly enhanced in the presence of H4SiW12O40. The major differences in temperature dependence observed between catalyzed and uncatalyzed nitrobenzene oxidation kinetics strongly suggest that the reaction path of H4SiW12O40-catalyzed supercritical water oxidation (average activation Ea=218 kJ/mol; k=0.015–0.806 s−1 energy for T=440–500 °C; Ea=134 kJ/mol for the temperature range T=470–490 °C) apparently differs from that of uncatalyzed supercritical water oxidation (Ea=212 kJ/mol; k=0.37–6.6 μM s−1). Similar primary oxidation products (i.e. phenol and 2-, 3-, and 4-nitrophenol) were identified for both treatment systems. H4SiW12O40-catalyzed homogenous nitrobenzene oxidation kinetics was not sensitive to the presence of OH scavengers.